2009
DOI: 10.1055/s-0029-1211774
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies of lipoprotein pattern and fibrinolysis in acromegalic patients: Relation to growth hormone levels and insulin-like growth factor I

Abstract: The influence of hGH and IGF-I levels on lipid-, lipoprotein metabolism and fibrinolysis were studied in 23 patients with active acromegaly (14 women and 9 men, mean age 49.8 +/- 2.1 years) compared to a sex, BMI and age-matched control group. Mean Lp(a) levels were significantly higher in acromegalics than in controls (469.8 +/- 140.1; n = 23 vs. 162.7 +/- 64.9 mg/l; n = 111; p < 0.01). We found elevated apolipoprotein A-I and Apo E-concentrations in acromegalic patients compared to controls (apo A-I: 1.79 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 18 publications
5
26
0
3
Order By: Relevance
“…Some small case-control studies suggested the presence of a prothrombotic tendency in acromegalic patients that might partially contribute to the development of cardiovascular complications (1). For example, in a small case-control study, Wildbrett et al (84) reported higher levels of plasma PAI-1 and t-PA in 23 patients with active acromegaly than in healthy controls. Moreover, a positive, significant association was observed between plasma insulin-like growth factor 1 (IGF1), GH, and PAI-1 levels among these patients (84).…”
Section: Acromegalymentioning
confidence: 99%
See 1 more Smart Citation
“…Some small case-control studies suggested the presence of a prothrombotic tendency in acromegalic patients that might partially contribute to the development of cardiovascular complications (1). For example, in a small case-control study, Wildbrett et al (84) reported higher levels of plasma PAI-1 and t-PA in 23 patients with active acromegaly than in healthy controls. Moreover, a positive, significant association was observed between plasma insulin-like growth factor 1 (IGF1), GH, and PAI-1 levels among these patients (84).…”
Section: Acromegalymentioning
confidence: 99%
“…For example, in a small case-control study, Wildbrett et al (84) reported higher levels of plasma PAI-1 and t-PA in 23 patients with active acromegaly than in healthy controls. Moreover, a positive, significant association was observed between plasma insulin-like growth factor 1 (IGF1), GH, and PAI-1 levels among these patients (84). Recently, Erem et al (6) reported higher plasma fibrinogen, antithrombin, and PAI-1 levels, and lower protein S activity and TFPI levels in 22 patients with active acromegaly than those in 22 age-matched healthy controls.…”
Section: Acromegalymentioning
confidence: 99%
“…Parallel und im Zusammenhang zu Störungen im Kohlenhydratstoffwechsel treten auch Veränderungen im Lipidstoffwechsel auf, im Sinne einer erhöhten Atherogenität: Hypertriglyzeridämie, erhöhte Apo-E-, Apo-AI-und Lp(a)-Konzentrationen sowie höhere "Small-dense-LDL-Subfraktionen" und postprandiale Lipoprotein-Remnant-Konzentrationen [26,29].…”
Section: Epidemiologieunclassified
“…GH stimulates apolipoprotein E (Apo-E) and apolipoprotein A-I (Apo A-I) secretion [47]. Moreover, elevated levels of serum lipoprotein (a) concentrations have been found in both active patients and in those with controlled disease [48].…”
Section: Biochemical Control Of Acromegaly and Effect On Metabolic Comentioning
confidence: 99%